Sine of Sum

From ProofWiki
Jump to: navigation, search

Theorem

$\map \sin {a + b} = \sin a \cos b + \cos a \sin b$

where $\sin$ denotes the sine and $\cos$ denotes the cosine.


Corollary

$\map \sin {a - b} = \sin a \cos b - \cos a \sin b$


Proof 1

\(\displaystyle \map \cos {a + b} + i \, \map \sin {a + b}\) \(=\) \(\displaystyle e^{i \paren {a + b} }\) Euler's Formula
\(\displaystyle \) \(=\) \(\displaystyle e^{i a} e^{i b}\) Exponential of Sum
\(\displaystyle \) \(=\) \(\displaystyle \paren {\cos a + i \sin a} \paren {\cos b + i \sin b}\) Euler's Formula
\(\displaystyle \) \(=\) \(\displaystyle \paren {\cos a \cos b - \sin a \sin b} + i \paren {\sin a \cos b + \cos a \sin b}\) Complex Numbers form Field

By equating the imaginary parts, the result follows.

$\blacksquare$


Proof 2

Recall the analytic definitions of sine and cosine:

$\displaystyle \sin x = \sum_{n \mathop = 0}^\infty \left({-1}\right)^n \frac {x^{2 n + 1}} {\left({2 n + 1}\right)!}$
$\displaystyle \cos x = \sum_{n \mathop = 0}^\infty \left({-1}\right)^n \frac {x^{2 n}} {\left({2 n}\right)!}$

Let:

\(\displaystyle g \left({a}\right)\) \(=\) \(\displaystyle \sin \left({a + b}\right) - \sin a \cos b - \cos a \sin b\)
\(\displaystyle h \left({a}\right)\) \(=\) \(\displaystyle \cos \left({a + b}\right) - \cos a \cos b + \sin a \sin b\)

Let us differentiate these with respect to $a$, keeping $b$ constant.

Then from Derivative of Sine Function and Derivative of Cosine Function, we have:

\(\displaystyle g' \left({a}\right)\) \(=\) \(\displaystyle \cos \left({a + b}\right) - \cos a \cos b + \sin a \sin b = h \left({a}\right)\)
\(\displaystyle h' \left({a}\right)\) \(=\) \(\displaystyle - \sin \left({a + b}\right) + \sin a \cos b + \cos a \sin b = - g \left({a}\right)\)

Hence:

\(\displaystyle D_a \left({\left({g \left({a}\right)}\right)^2 + \left({h \left({a}\right)}\right)^2}\right)\) \(=\) \(\displaystyle 2 g \left({a}\right) g' \left({a}\right) + 2 h \left({a}\right) h' \left({a}\right)\)
\(\displaystyle \) \(=\) \(\displaystyle 0\)

Thus from Derivative of Constant:

$\forall a \in \R: g \left({a}\right)^2 + h \left({a}\right)^2 = c$

In particular, it is true for $a = 0$, and so:

$g \left({0}\right)^2 + h \left({0}\right)^2 = 0$

So:

$g \left({a}\right)^2 + h \left({a}\right)^2 = 0$

But from Square of Real Number is Non-Negative:

$g \left({a}\right)^2 \ge 0$ and $h \left({a}\right)^2 \ge 0$

So it follows that:

$g \left({a}\right) = 0$

and:

$h \left({a}\right) = 0$

Hence the result.

$\blacksquare$


Proof 3

\(\displaystyle \sin a \cos b + \cos a \sin b\) \(=\) \(\displaystyle \paren {\frac {e^{i a} - e^{-i a} }{2 i} } \cos b + \cos a \paren {\frac {e^{i b} - e^{-i b} }{2 i} }\) Sine Exponential Formulation
\(\displaystyle \) \(=\) \(\displaystyle \paren {\frac {e^{i a} - e^{-i a} } {2 i} } \paren {\frac {e^{i b} + e^{-i b} } 2} + \paren {\frac {e^{i a} + e^{-i a} } 2} \paren {\frac {e^{i b} - e^{-i b} } {2 i} }\) Cosine Exponential Formulation
\(\displaystyle \) \(=\) \(\displaystyle \frac {e^{i a} e^{i b} + e^{i a} e^{-i b} - e^{-i a} e^{i b} - e^{-i a} e^{-i b} } {4 i}\) expanding
\(\displaystyle \) \(\) \(\, \displaystyle + \, \) \(\displaystyle \frac {e^{i a} e^{i b} - e^{i a} e^{-i b} + e^{-i a} e^{i b} - e^{-i a} e^{-i b} } {4 i}\)
\(\displaystyle \) \(=\) \(\displaystyle \frac {e^{i a} e^{i b} - e^{-i a} e^{-i b} } {2 i}\) sinplifying
\(\displaystyle \) \(=\) \(\displaystyle \frac {e^{i \paren {a + b} } - e^{-i \paren {a + b} } } {2 i}\) Exponential of Sum
\(\displaystyle \) \(=\) \(\displaystyle \map \sin {a + b}\) Sine Exponential Formulation

$\blacksquare$


Proof 4

\(\displaystyle \sin \left({a + b}\right)\) \(=\) \(\displaystyle \cos \left({\frac \pi 2 - \left({a + b}\right)}\right)\) Cosine of Complement equals Sine
\(\displaystyle \) \(=\) \(\displaystyle \cos \left({\left({\frac \pi 2 - a}\right) - b}\right)\)
\(\displaystyle \) \(=\) \(\displaystyle \cos \left({\frac \pi 2 - a}\right) \cos b + \sin \left({\frac \pi 2 - a}\right) \sin b\) Cosine of Difference
\(\displaystyle \) \(=\) \(\displaystyle \sin a \cos b + \sin \left({\frac \pi 2 - a}\right) \sin b\) Cosine of Complement equals Sine
\(\displaystyle \) \(=\) \(\displaystyle \sin a \cos b + \cos a \sin b\) Sine of Complement equals Cosine

$\blacksquare$


Proof 5

\((1):\quad\) \(\displaystyle 2 \sin a \cos b\) \(=\) \(\displaystyle \sin \paren {a + b} + \sin \paren {a - b}\) Simpson's Formula for Sine by Cosine: Proof 2
\((2):\quad\) \(\displaystyle 2 \cos a \sin b\) \(=\) \(\displaystyle \sin \paren {a + b} - \sin \paren {a - b}\) Simpson's Formula for Cosine by Sine: Proof 2
\(\displaystyle \leadsto \ \ \) \(\displaystyle 2 \sin \paren {a + b}\) \(=\) \(\displaystyle 2 \sin a \cos b + 2 \cos a \sin b\) $(1) + (2)$
\(\displaystyle \leadsto \ \ \) \(\displaystyle \sin \paren {a + b}\) \(=\) \(\displaystyle \sin a \cos b + \cos a \sin b\)

$\blacksquare$


Historical Note

The Sine of Sum formula and its corollary were proved by François Viète in about $1579$.


Also see


Sources